Current status and future trends in Cryptosporidium and Giardia epidemiology in Malaysia - Lim, Yvonne Ai Lian; Ahmad, R.A.; Smith, H.V. (IWA Publishing, 2008)
Cryptosporidium and Giardia are major causes of diarrhoeal diseases of humans worldwide, and are included in the World Health Organisation's 'Neglected Diseases initiative'. Cryptosporidium and Giardia occur commonly in Malaysian human and non-human populations, but their impact on disease, morbidity and cost of illness is not known. The commonness of contributions from human (STW effluents, indiscriminate defaecation) and non-human (calving, lambing, muck spreading, slurry spraying, pasturing/grazing of domestic animals, infected wild animals) hosts indicate that many Malaysian environments, particularly water and soil, are sufficiently contaminated to act as potential vehicles for the transmission of disease. To gain insight into the morbidity and mortality caused by human cryptosporidiosis and giardiasis, they should be included into differential diagnoses, and routine laboratory testing should be performed and (as for many infectious diseases) reported to a centralised public health agency. To understand transmission routes and the significance of environmental contamination better will require further multidisciplinary approaches and shared resources, including raising national perceptions of the parasitological quality of drinking water. Here, the detection of cryptosporidium and Giardia should be an integral part of the water quality requirement. A multidisciplinary approach among public health professionals in the water industry and other relevant health- and environment-associated agencies is also required in order to determine the significance of Ctyptosporidium and Giardia contamination of Malaysian drinking water. Lastly, adoption of validated methods to determine the species, genotype and subgenotype of Cryptosporidium and Giardia present in Malaysia will assist in developing effective risk assessment, management and communication models.